Biogenic synthesis of copper nanoparticles using Borreria hispida (Linn.) extract and its antioxidant activity. (2020) - Venugopalan, Rajasudha; Pitchai, Sakunthala; Devarayan, Kesavan; Swaminathan, Vinobha Chinnaiah
Abstract: The present study describes biosynthesis of copper nanoparticles using the Borreria hispida (Linn .) plant extract. At first, the crude extract was extracted from the dried whole plant Borreria hispida (Linn .) using methanol. Then the extract was used to synthesis copper nanoparticles. The morphology and elemental composition of the synthesized copper nanoparticles were observed using scanning electron microscopy coupled with energy dispersive spectrum. The copper nanoparticles were having size between 84 and 158 nm. The X-ray diffraction pattern confirmed the presence of metallic copper nanoparticles and absence of copper oxide. Further the copper nanoparticles exhibited significant anti-oxidant activity.